Alberta Rating Index for Apps: Study of Reliability and Validity. (September 2022) - Azad-Khaneghah, Peyman; Roduta Roberts, Mary; Liu, Lili
Background. The number of mobile health applications is rapidly increasing, yet no reliable tool exists for occupational therapists and their clients to rate the quality of these apps.Purpose . To develop the Alberta Rating Index for Apps (ARIA).Methods. Through a sequential design in three phases, we developed a rating index for mobile health applications and examined its reliability and validity with 10 participants.Findings. The coefficients of reliability were 0.95 for occupational therapists, 0.60 for older adults, and 0.88 for adults with a mental health condition. ARIA's correlation with another scale used in app review studies, U-MARS, was low to moderate.Implications. ARIA showed a high inter-rater reliability in two of the three user groups. ARIA is comprehensive and includes criteria not captured by U-MARS, such as privacy and security. Further studies are warranted with diverse raters and health apps.